1995
DOI: 10.1143/jjap.34.5077
|View full text |Cite
|
Sign up to set email alerts
|

Surface Morphologies and Electrical Properties of (Ba, Sr)TiO3 Films Prepared by Two-Step Deposition of Liquid Source Chemical Vapor Deposition

Abstract: Protrusions of (Ba, Sr)TiO3 (BST) crystallites were found to appear on BST film surfaces prepared by liquid source chemical vapor deposition (CVD) at a substrate temperature T s=420° C and a reactor pressure P=1.5 Torr. Such protrusions were successfully suppressed by two-step deposition, where BST films consisted of a buffer layer and a main layer; the buffer layer was a CVD-BST film about 60 Å thick annealed in N2 ambient. By this two-step deposition on Pt electrodes, the BST film prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(24 citation statements)
references
References 6 publications
1
23
0
Order By: Relevance
“…There is generally quite good agreement with published values of the dielectric constant ͑DK͒ of as-deposited films, 3,11,12,25,[30][31][32][33] however, a detailed comparison is reasonable only for larger thickness series. In addition, the limited range of the linear 1 / C behavior, which has been observed by different groups, corroborates this comparison; a flatting of the slope of the 1 / C curve is observed at larger thickness 11,33 as well as an increase of the slope.…”
Section: A Homogeneous Filmssupporting
confidence: 81%
“…There is generally quite good agreement with published values of the dielectric constant ͑DK͒ of as-deposited films, 3,11,12,25,[30][31][32][33] however, a detailed comparison is reasonable only for larger thickness series. In addition, the limited range of the linear 1 / C behavior, which has been observed by different groups, corroborates this comparison; a flatting of the slope of the 1 / C curve is observed at larger thickness 11,33 as well as an increase of the slope.…”
Section: A Homogeneous Filmssupporting
confidence: 81%
“…Even further improvements were achieved by using a four step process of deposition of an ultrathin seed layer (6 nm), N2 rapid thermal anneal, deposition of the rest of the BST, followed by a final N2 thermal anneal [56]. The properties obtained these different approaches are shown in Figure 22 [56]. The capacitance density is basically the same but the reported l~age current densities are lower for two deposition steps compared to just one.…”
Section: Low Temperature Mocvd Bstmentioning
confidence: 99%
“…This process achieved following the properties teq = 0.51 nm, J(1.1V) = 6.6 10-8 A/cm 2 , tan(8) = 0.007, and step coverage = 0.8 [54]. Even further improvements were achieved by using a four step process of deposition of an ultrathin seed layer (6 nm), N2 rapid thermal anneal, deposition of the rest of the BST, followed by a final N2 thermal anneal [56]. The properties obtained these different approaches are shown in Figure 22 [56].…”
Section: Low Temperature Mocvd Bstmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Kawahara et al observed many surface protrusions in dielectric bismuth strontium titanate (BST) films prepared by CVD. [10] The origin of these surface defects was ascribed to insufficient crystallization during the film deposition, and a two-step deposition process was proposed to hinder defect formation. Kim and Lee reported on significantly improved dielectric constant and leakage current density in a hillock-free BST film.…”
Section: Introductionmentioning
confidence: 99%